STUDENTS’ PERSPECTIVE TOWARD THE IMPLEMENTATION OF GOOGLE FORM AS A DIGITAL LEARNING ASSESSMENT TOOL - Nursani; Zaiturrahmi; Diana, Novita (IPI Garut Press, 2024)
The purpose of this research is to describe students' perspectives on the implementation of Google Forms as a digital assessment tool. This research uses a qualitative research design. Data collection was carried out through questionnaires and interviews. The research participants were 20 students in the second grade at Dassa Al-Aziziyah Islamic Senior High School. Data from 20 questions were distributed, and interviews with eight students were analyzed. Results were produced regarding students' perspectives on implementing Google Forms as a digital learning assessment tool. The research results showed that students have a positive perspective on using Google Forms from attractiveness, effectiveness, convenience, and efficiency. The efficiency aspect allows students to know the score directly. Thus, this provides efficiency and accuracy to the assessment system. Additionally, it makes it easy for students to answer questions by clicking on the answer rather than circling the question. Moreover, mandatory questions help students to fill in all the questions before submitting the test. Therefore, this will ensure that questions are answered. However, students have a negative perspective on using Google Forms regarding accessibility.